DESIGN OF AN INTERNET OF THINGS-BASED WATER LEVEL MONITORING SYSTEM - Rienandie, Naufal Fakhrie; Pramudita, Resa (Universitas Royal, 2025)
Abstract: Conventional water reservoir filling systems often cause inefficiencies due to delays in monitoring or failure of the float system which results in overflowing water from the reservoir. this research aims to develop an ESP32-based water level monitoring and control system by utilising IoT technology and ultrasonic sensors, this system can facilitate users in monitoring water levels and automating pump control. this research uses the experimental method, starting from system design to system testing and analysis, as well as testing which includes sensor accuracy, system response, and communication stability with the IoT server. based on the results obtained. The test results show that the system has an average accuracy rate of 98.4% with an average response time of 1.8 seconds. based on the results obtained, this system shows a positive accuracy value and response time in its application. Keywords: blynk; internet of things; monitoring; water level Abstrak: Sistem pengisian tandon air secara konvensional sering kali menimbulkan ketidakefisienan karena keterlambatan dalam pemantauan atau kegagalan sistem pelampung yang mengakibatkan meluapnya air dari tandon. penelitian ini bertujuan untuk mengembangkan sistem monitoring dan kontrol ketinggian air berbasis ESP32 dengan memanfaatkan teknologi IoT dan sensor ultrasonik, sistem ini dapat memudahkan pengguna dalam memonitoring ketinggian air dan mengotomatisasi kontrol pompa. Penelitian ini menggunakan metode eksperimen, mulai dari perancangan sistem hingga pengujian dan analisis sistem, serta pengujian yang meliputi akurasi sensor, respon sistem, dan kestabilan komunikasi dengan server IoT. Hasil pengujian menunjukkan bahwa sistem memiliki tingkat akurasi rata-rata sebesar 98,4% dengan waktu respon rata-rata 1,8 detik. berdasarkan hasil yang diperoleh, sistem ini menunjukkan nilai akurasi dan waktu respon yang positif dalam pengaplikasiannya. Kata kunci: blynk; internet of things; pemantauan; tingkat air